Characterizing breathing dynamics of magnetic skyrmions and antiskyrmions within the Hamiltonian formalism - Mckeever, B. F.; Rodrigues, D. R.; Pinna, Daniele; Abanov, Ar; Sinova, Jairo; Everschor-Sitte, Karin (Physical Review B, 2019)
We derive an effective Hamiltonian system describing the low-energy dynamics of circular magnetic skyrmions and antiskyrmions. Using scaling and symmetry arguments, we model (anti)skyrmion dynamics through a finite set of coupled, canonically conjugated, collective coordinates. The resulting theoretical description is independent of both micromagnetic details as well as any specificity in the ansatz of the skyrmion profile. Based on the Hamiltonian structure, we derive a general description for breathing dynamics of (anti)skyrmions in the limit of radius much larger than the domain wall width. The effective energy landscape reveals two qualitatively different types of breathing behavior. For small energy perturbations, we reproduce the well-known small breathing mode excitations, where the magnetic moments of the skyrmion oscillate around their equilibrium solution. At higher energies, we find a breathing behavior where the skyrmion phase continuously precesses, transforming Néel to Bloch skyrmions and vice versa. For a damped system, we observe the transition from the continuously rotating and breathing skyrmion into the oscillatory one. We analyze the characteristic frequencies of both breathing types, as well as their amplitudes and distinct energy dissipation rates. For rotational (oscillatory) breathing modes, we predict on average a linear (exponential) decay in energy. We argue that this stark difference in dissipative behavior should be observable in the frequency spectrum of excited (anti)skyrmions.
CRIS-Team Scopus Importer:2023-03-27